(untitled) (Research, Society and Development, 2023)
Diabetic neuropathy is a feeling of diabetes mellitus resulting from nerve damage caused by the hyperglycemic state in the body, generating long-term deficiencies. Disease diagnosed late in the public health system (SUS). The aim of the study was to show the importance of early implementation of diabetic neuropathy screening in the SUS, seeking to prevent complications and establish effective treatment measures. This is an integrative review, where articles researched during 3 months, dated between 2015 and 2022 were used. The inclusion criteria in the analysis sample were: 1) articles with publication data from 2015; 2) articles recognized by experts in the field of family medicine and neurology. Exclusion criteria were: duplicate articles, monographs, course conclusion works and book chapters. Thus, much of the research suggests that most of the symptoms of diabetic neuropathy appear progressively and slowly, making it difficult to diagnose early. Thus, an effective strategy for the public health program is to prevent and control diabetes, in addition to using innovative screening methods, such as frequent sensitivity tests using monofilaments, tuning forks, biotensiometers and the neuropathic impairment score, which are essential for suspected pathogenesis.